Does Poor Health Increase the Likelihood of Flexible Employment? - Flavel, Joanne (My University, 2016)
This paper examines the effect of health and health shocks on form of employment for the Australian working age population using fourteen waves of the Household, Income and Labour Dynamics in Australia Survey (2001-2014). Dynamic multilevel multinomial modelling methods are used to account for initial condition, state dependence and unobserved heterogeneity. The results show that poor health, measured by a constructed health index, significantly increases the likelihood of part time and casual employment, with the effect being larger for men and for part time employment. The greater effect of health and health shocks is on reducing the likelihood of employment
NILS Working Paper
Keywords: Employment; Health; Labour market; Health and wellbeing; Health; Employment; Employment and unemployment; Health and wellbeing